Permintaan Pasar untuk Produk dan Layanan Energi Terbarukan (Perspektif Daya Saing Energi Terbarukan Indonesia) - Nurfiani Syamsuddin; Syaifuddin Yana; Nelly Nelly; Maryam Maryam; Fitriliana Fitriliana; Arsyad Arsyad (Fakultas Teknik, 2023)
To meet its domestic energy demands, Indonesia continues to minimize its reliance on fossil fuels and rely more on renewable energy sources. This is done to guarantee that the energy is distributed evenly throughout the area. Given the potential and availability of renewable energy sources in nature, Indonesia can meet the EBT mix target of 23% in 2025 and 31% in 2030. It’s only that attaining the EBT mix target is difficult; Indonesia faces numerous hurdles. As a result, based on the most recent books and research, this study addresses the obstacles that Indonesia faces in meeting market demand for new and renewable energy goods and services. These obstacles, it is anticipated, would subsequently push Indonesia to take bold moves in rejuvenating the energy sector, strategic policies, and major investment.